Textbook on Indian penal code - "Gaur, K. D" (Delhi, 2014)
The present edition is a unique exercise to project the latest innovations which have culled through judicial and administrative techniques of creativity. The book is an attempt has been made to make the discussion throughout clear, lucid, brief and logical. Leading and illustrative cases have been included so that the basic principles of criminal jurisprudence get stamped on the memory of the readers.
Keywords: Penal code - India